2019
DOI: 10.1590/0100-29452019097
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics of jabuticaba pulp by regression models

Abstract: Jabuticaba tree is native to the Atlantic Forest in Southern Brazil, and its fruit is widely consumed in the fresh form, but it is highly perishable, requiring conservation techniques. The aim of this study was to describe the drying kinetics of jabuticaba pulp at temperatures of 50 and 60°C, comparing the Henderson, Simple Three-Parameter Exponential, Lewis, Thompson, Fick and Wang and Sing regression models and estimating the Absolute Drying Rate (ADR) for the best model. Parameters were estimated using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…The graphical analysis showed that the residuals did not follow random behavior under all conditions for both models, which means that the error terms are not independent. Furtado et al (2019), who found a similar result in the description of the drying kinetics of jabuticaba pulp at 50 and 60°C, explained that the presence of autocorrelated errors in the adjustment of nonlinear regression models may be associated with the fact that all measurements were made on the same material throughout of time. Despite this, for both models, the Shapiro–Wilk test was not significant for the two models so the data are, at least approximately, from a normal distribution at the 5% significance level.…”
Section: Resultsmentioning
confidence: 79%
“…The graphical analysis showed that the residuals did not follow random behavior under all conditions for both models, which means that the error terms are not independent. Furtado et al (2019), who found a similar result in the description of the drying kinetics of jabuticaba pulp at 50 and 60°C, explained that the presence of autocorrelated errors in the adjustment of nonlinear regression models may be associated with the fact that all measurements were made on the same material throughout of time. Despite this, for both models, the Shapiro–Wilk test was not significant for the two models so the data are, at least approximately, from a normal distribution at the 5% significance level.…”
Section: Resultsmentioning
confidence: 79%
“…The Durbin Watson test was applied to verify the presence of residual dependence between the measures, evaluating if the residue of an observation is associated with the residue of the adjacent observations (FURTADO et al, 2019). The Breusch-Pagam test was used to verify the homogeneity of residues, and the Shapiro-Wilk test was used to verify their normality.…”
Section: Methodsmentioning
confidence: 99%
“…A cinética de secagem de grãos representa a velocidade do decréscimo do teor de água do produto em relação ao tempo (BOTELHO et al, 2018;FURTADO et al, 2019a, FURTADO et al, 2019b. Esta perda de água pode ser representada por uma curva de caráter sigmoidal decrescente que é característica de modelos de regressão não linear.…”
Section: Os Modelos Matemáticos São Ferramentas Importantes Na Estima...unclassified